Correlation of Vitamin D Levels with Pigmentation in Vitiligo Patients Treated with NBUVB Therapy. (23rd March 2014) - Sehrawat, Manu; Arora, Tarlok Chand; Chauhan, Amrita; Kar, Hemanta Kumar; Poonia, Amitabh; Jairath, Vijayeeta
Abstract : Cholecalciferol (vitamin D) might play a physiological role in photo-induced melanogenesis in human skin. We estimated the levels of 25-hydroxy vitamin D [25(OH)D] before, during, and after Narrow Band Ultraviolet B (NBUVB) radiation in patients of vitiligo and their correlation with NBUVB induced pigmentation. Thirty patients of vitiligo and equal number of age and sex matched controls were recruited for the study. Vitiligo patients were treated with NBUVB thrice weekly for 12 weeks. [25(OH)D] levels and Vitiligo Area and Severity Index (VASI) were calculated at 0 (baseline), 6, and 12 weeks. Baseline [25(OH)D] levels were measured in controls. Significant reduction in VASI score was observed after 12 weeks of therapy. Comparison and correlation between mean improvement in VASI and [25(OH)D] levels at 12 weeks showed moderate correlation, and the results were statistically insignificant. Mean reduction in VASI and increase in [25(OH)D] levels after 12 weeks of NBUVB showed moderate correlation. Thus, vitamin D might play a significant role in photo-induced melanogenesis. However, there might be additional effects of the phototherapy on melanogenesis. The complete mechanism of NBUVB induced pigmentation in vitiligo needs to be elucidated.